A phase I drug-drug interaction study to assess the effect of futibatinib on P‐gp and BCRP substrates and of P‐gp inhibition on the pharmacokinetics of futibatinib - Amanda Long; Ikuo Yamamiya; Michelle Valentine; Ziv Machnes; Nanae Hangai; Bailey Anderson; Volker Wacheck; Ling Gao (Wiley, 2024)
Abstract Futibatinib, an inhibitor of fibroblast growth factor receptor 1-4, is approved for the treatment of patients with advanced cholangiocarcinoma with FGFR2 fusions/rearrangements. In this phase I drug-drug interaction study, the effects of futibatinib on P‐glycoprotein (P‐gp) and breast cancer resistance protein (BCRP) substrates, and of P‐gp inhibition on futibatinib pharmacokinetics (PK) were investigated in healthy adults aged 18-55 years. In part 1, 20 participants received digoxin (P‐gp substrate) and rosuvastatin (BCRP substrate). Following a ≥10‐day washout, futibatinib was administered for 7 days, with digoxin and rosuvastatin coadministered on the third day. In part 2, 24 participants received futibatinib. Following a ≥3‐day washout, quinidine (P‐gp inhibitor) was administered for 4 days, with futibatinib coadministered on day 4. Blood samples were collected predose and for 24 (futibatinib), 72 (rosuvastatin), and 120 h (digoxin) postdose. Urine samples (digoxin) were collected predose and for 120 h postdose. PK parameters were compared between treatments using analysis of variance. Coadministration with futibatinib had no effect on the PK of digoxin and rosuvastatin, and coadministration with quinidine had minimal effects on the PK of futibatinib. Differences in Cmax and AUC with and without futibatinib and quinidine, respectively, were <20%. The most common treatment‐emergent adverse events were diarrhea (80%) and increased blood phosphorous (75%) in part 1 and prolonged electrocardiogram QT interval (38%) in part 2. The data show that futibatinib has no clinically meaningful effects on the PK of P‐gp or BCRP substrates and that the effect of P‐gp inhibition on futibatinib PK is not clinically relevant.